The Impact of Experiential Marketing, Brand Ambassador, and Product Quality on Scarlett Whitening Customer Loyalty - Rahma, Fijri Aulia; Nuvriasari, Audita (Formosa Journal of Multidisciplinary Research, 2024)
This study examines the impact of Experiential Marketing, Brand Ambassador, and Product Quality on Customer Loyalty of Scarlett Whitening. A sample of 100 respondents was selected using purposive sampling and questionnaires. This research uses explanatory quantitative research methods. The findings of this study demonstrate that: (1) Experiential Marketing does not have a significant impact on Customer Loyalty for Scarlett Whitening, (2) Brand Ambassador has a significant and positive impact on Customer Loyalty for Scarlett Whitening, (3) Product Quality has a significant and positive impact on Customer Loyalty for Scarlett Whitening.